Classification of State Regulation Principles in the Field of Air Transport - O. V. Brusakova (Law and Safety)
It has been established that the principles of state regulation in the field of air transport can be defined as an objectively determined set of basic requirements, rules and standards, compliance with which is ensured by state coercive force, which are key guidelines for streamlining with the use of regulatory measures of public and legal relations between subjects and objects of aviation activity and provision of aviation services.